Digital Transformation in Public Services: Evaluation of E-Government Implementation in Indonesia - Erlita Khrisinta Dewi; Yosi Muhaemin; Gabriel Amadeus Sitompul; Ramadha Yanti Parinduri; Marsiana Rika (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to determine the digital transformation in public services: an evaluation of e-government implementation in Indonesia. This study uses an evaluative study with a qualitative approach. Informants were selected using purposive sampling, including policymakers, technical implementers, and service users. Data were obtained through in-depth interviews, participant observation, and documentation studies. The results of this study indicate that the evaluation of e-government implementation in Indonesia shows significant progress in digital infrastructure, public services, and public participation. However, challenges such as the digital divide between regions, limited civil servant competency, uneven system integration, and data security risks still need to be addressed. Therefore, strategies are needed to strengthen e-government, including cross-sector data integration, increased digital literacy, and strengthened cybersecurity, which are expected to improve bureaucratic efficiency, service quality, public trust, and community participation.